2012
DOI: 10.3329/bjar.v36i4.11761
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Nutrient Management for Potatomungbean- T.Aman Rice Cropping Pattern Under Level Barind Agroecological Zone

Abstract: A field experiment was conducted at the Multiplication Testing Site (MLT), Joypurhat Sadar upazila with Potato-Mugnbean -T. Aman rice cropping pattern during November/2007 to November/2008 to verify different nutrient management approaches and to determine the economic dose of fertilizer for the said cropping pattern. The experiment was designed with five treatments for whole of the cropping pattern in a randomized complete block design with six replications. The treatments were, soil test based fertilizer dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Sufficient and balanced application of organic and inorganic fertilizers is a major component of INM [24,43]. Successful INM extension will also require greater monitoring and testing of plants and soils [25,31]. Monitoring will help ensure that an environment conducive for optimal plant growth and crop yield can be established through nutrient application and soil reclamation [29,31,43].…”
Section: Volume 4 Issue 2 -2016mentioning
confidence: 99%
See 1 more Smart Citation
“…Sufficient and balanced application of organic and inorganic fertilizers is a major component of INM [24,43]. Successful INM extension will also require greater monitoring and testing of plants and soils [25,31]. Monitoring will help ensure that an environment conducive for optimal plant growth and crop yield can be established through nutrient application and soil reclamation [29,31,43].…”
Section: Volume 4 Issue 2 -2016mentioning
confidence: 99%
“…In addition to the primary nutrients, less intensively used secondary nutrients (sulfur, calcium, and magnesium) are necessary as well [18][19][20][21][22]. A number of micronutrients such as chlorine, iron, manganese, zinc, copper, boron, and molybdenum also influence plant growth [23][24][25]. These micronutrients are required in small amounts (ranging from a few grams to a few hundred grams per hectare) for the proper functioning of plant metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Sarkar et al (2014) also indicated the highest number of effective tillers hill -1 , grains panicle -1 , panicle length and grain yield were recorded in the treatment using 75% recommended dose of fertilizer. Mollah et al (2011) found that cow dung had a positive effect on grain and straw yields of Aman rice.…”
Section: Grain Yieldmentioning
confidence: 96%
“…Producing FYM in situ by integrating animals into the rice-based cropping system, as generally seen in coastal areas of India, may make this possible. Applying organic manure on the basis of its major nutrient concentrations rather than using bulk quantity, as is generally done by farmers in South Asia (Barik et al, 2006), and replacing a portion of chemical fertilizers by organic manure on the basis of soil test-based fertilizer dose (Mollah et al, 2007), are steps toward a more sensible use of organic sources to make them more economically sound for coastal farmers.…”
Section: Nutrient Managementmentioning
confidence: 99%